Algebra :\
posted by Presley .
Elimination using addition and subtraction:
1.
x  y = 1
x + y = 3
2.
x + y = 1
x + y = 11
3.
x + 4y = 11
x  6y = 11
4.
x + 3y = 6
x + 3y = 18
PLEASE HELP!!!!
I NEED HELP ASAP!!!!

Either add or subtract one equation from the other to eliminate x.
For example. ADD the two equations in Problem 1. This results in 2x = 4, which requires that x = 2. Use either equation to get y.
You can certainly do the others yourself.
Respond to this Question
Similar Questions

Math
Using the definition of subtraction to determine the subtraction equations that are related to each of the following addition equation: a.8+7=n b.14+x=25 c.r+s=t my answers are this: a. n7=8 b.x=2514 c.ts=r did I do these right? 
MATH 156
What models can be used to help explain the concepts of addition and subtraction of rational numbers? 
Very easy math
my teacher told me that the inverse of addition was subtraction and that the inverse of subtraction was addition... could you prove it to me x = (1)x ((1)x)^1 I don't see how I'm suppose to get + x by taking the inverse of x i've … 
algebra 1A
could someone write me an expression using three of the following? 
Algebra
Solve the following systems of equations using the addition (elimination) method. 2x+3y=5 2xy=1 
Algebra
Solve the following systems of equations using the addition (elimination) method. 5x+y=2 3x+y=1 
Algebra
Solve the following systems of equations using the addition (elimination) method. 5x=20+y 16=3y+4x 
MATH
HOW IS ADDITION & SUBTRACTION OF POLYNOMIALS SIMILAR TO ADDITION & SUBTRACTION OF RADICAL EXPRESSIONS? 
Algebra
To solve the following system of equations by elimination, which operation would you perform first? 
Math
How is combing radicals by addition and subtraction similar to combining monomial expressions by addition and subtraction?